Gender and Age Proportion of Mycobacterium Tuberculosis Detection Using Nested Real Time Polymerase Chain Reaction at Indramayu District General Hospital - Indriani Silvia; Kati Sriwiyati; Cantika Widia Astuti; Ghina Sofiana; Sania Putri Tresna Sari, (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
Background: Tuberculosis (TB) is an infectious disease caused by Mycobacterium Tuberculosis (MTB) also the second cause of death among all infectious diseases in the world. World Health Organization (WHO) and lots studies have conclude that the risk of tuberculosis (TB) increases dramatically during young adult and males. Objective: To analyse the proportion of gender and age of MTB detected using hemi-nested RT PCR. Methods: This study used a descriptive method by taking 97 patients secondary data from the Indramayu General Hospital. Results: of 97 data showed 37 (38.1%) MTB positive patients. The proportion of rifampicin-sensitive (RS) positive MTB was (91.9%), in the age group 0-5 years (0%), 6-11 years (0%), 12-16 years (2.7%), 17-25 years (16.2%), 26-35 years (27%), 36-45 years (16.2%), 46-55 years (8.1%), 56-65 years (16.2%), >65 years (13.6%) and 54% in men. Rifampicin resistant (RR) as much as (5.4%) in the age group 56-65 years (2.7%) and age >65 years (2.7%) in men (5.4%). Rifampicin indeterminate (RI) (2.7%) was found at the age of 17-25 years in females (2.7%). Conclusion: The MTB detected proportion was mostly at the young adults of 26-35 years (27%), and based on gender, most were male (54%). Patients with RR were found at the age of >56 years and all were male.